The use of a candidate gene approach to study Botrytis cinerea resistance in Gerbera hybrida - Fu, Yiqian; Song, Yin; van Tuyl, Jaap M.; Visser, Richard G. F.; Arens, Paul (Frontiers in Plant Science, 2023)
Candidate genes (CG) for Botrytis cinerea resistance described in literature were mapped on gerbera linkage maps for which several QTL for Botrytis resistance had been found previously using a rapid, low-cost platform for SNP genotyping. In total, 29 CGs were mapped in either of two mapping populations. Four CGs were mapped within the previous identified QTL intervals and three co-localized with QTL. Two of these CGs for resistance against B. cinerea, PG1 (polygalacturonase gene) and sit (sitiens, ABA-aldehyde oxidase gene) that mapped in QTL regions for the ray floret disease resistance test were studied in detail. Virus-induced gene silencing (VIGS) was used for gene function analysis to determine the CGs’ role in gerbera resistance to Botrytis. Ray florets, of which the CGs were silenced, showed a significantly delayed growth of lesions upon Botrytis infection compared to controls. Combining QTL analysis, candidate gene mapping and VIGS showed to be an useful combination to identify possible causal genes and for understanding the molecular mechanisms of Botrytis resistance in gerbera. The two genes seem to act as partial S-genes and are likely among the determining genes leading to the variation observed for B. cinerea resistance in gerbera.